(De)criminalization of Survivors of Domestic Minor Sex Trafficking: A Social Work Call to Action. Issue 3 (20th June 2021) - Gezinski, Lindsay B
Abstract: Survivors of domestic minor sex trafficking (DMST) are failing to be identified and are frequently criminalized. Examining the linkages between DMST and the juvenile legal system is important, as many trafficked youths are only identified after entry into the child welfare or juvenile court system as a result of being arrested or detained on related delinquency charges. Due to legacies of structural violence, marginalized youths are reluctant to approach police officers for help. Therefore, social workers have an opportunity to identify, intervene, and advocate for trafficked youths. In this article, the author provides an overview of existing research related to the demographic profile of DMST, homelessness and survival sex, recruitment and entry, barriers to effective community response, and prevention and intervention strategies. This article represents a call to broaden our view of young people in the sex trade and supports the decriminalization of trafficked youths. Interventions and policies must be designed to fit their complex needs and experiences, resulting in empowerment, opportunity, and new beginnings.